Regulation 2016/1103, with occasion of commentary of the Judgment of the Appeal Court of Barcelona, 7th May 2019 - Rodríguez Rodrigo, Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
IIn the judgment object of comment, the Appeal Court of Barcelona applies article 9.2 Spanish Civil Code to determine the law of the matrimonial property regime related to a different nationality couple. Due to the circumstances of the case, the concurrent connection is the third of the mentioned precept. We have taken advantage of the commentary of this judgment to analyze the legal framework applicable by Spanish judges, regarding international jurisdiction and applicable law, in the following two contexts. On the one hand, we have assumed that the action is brought after January 29, 2019 and that the marriage has also been held after that date. In this situation, the Regulation 2016/1103 would be applicable, both to determine international jurisdiction and to specify the applicable law. On the other hand, let’s analyze the real assumption of the case under review, which is that the lawsuit was brought before January 29, 2019 and that the marriage was also held before that time. In this context, the Spanish judge should have applied the internal production text, to know if he had jurisdiction in the case, and the Spanish judge applied article 9.2 Spanish Civil Code, in the sector of the applicable law. In this last case, because we can deduce the data of the case, that the couple has not established a matrimonial property agreement.